Effects of an integrative warm-up method on the range of motion, core stability, and quality of squat performance of young adults - Šćepanović, Tijana; Kojić, Miloš; Mikić, Mladen; Štajer, Valdemar; Ödek, Uğur; Penjak, Ana (Frontiers in Sports and Active Living, 2024)
Introduction This research aims to determine the effects of an integrative warm-up method on the range of motion in joints of the lower extremities, the strength of the stabilizer trunk muscles, and the quality of the basic movement patterns in older adolescents. Methods The study sample consisted of 88 male students (age 20.1 ± 0.5). They were randomly divided into four groups: one control group (CG) (n = 17; 180.8 ± 7.9 cm; 82.3 ± 8.3 kg) and three experimental groups (EG): EG1 (n = 23; 180.9 ± 7.0 cm; 78.5 ± 9.5 kg), EG2 (n = 31; 182.2 cm ± 7.3 cm; 79.5 ± 11.5 kg), and EG3 (n = 17; 183.3 ± 4.9 cm; 77.5 ± 11.8 kg). The participants were subjected to a 6-week experimental treatment: EG1 once, EG2 twice, and EG3 three times a week. The experimental treatment consisted of four sub-phases representing the integrative warm-up Method: 1) Inhibition (self-myofascial release using a foam roller); 2) Lengthening (Static stretching in a maximum range of motion position); 3) Activation (Positional isometrics muscle activation of the trunk and gluteus); 4) Integration (Integrated all the previous phases into one complex movement pattern). Based on the covariance analysis (ANCOVA), statistically significant treatment effects were observed and positive changes were determined in all experimental groups. Results The differences between groups were observed in the following variables: Overhead Squat Assessment (p = 0.000; ηp2=0.318), range of motion of left hip flexion (p = 0.000; ηp2=0.371), range of motion of right hip flexion (p = 0.000; ηp2=0.051) and range of motion of right hip extension (p = 0.051; ηp2=0.088), Double Leg Lowering Test (F = 2.411; p = 0.014; ηp2=0.014) and range of combined motion (plantar and dorsiflexion) of left ankle joint (p = 0.000; ηp2=0.299). There was no significant difference in the Plank Test (F = 1.007; p = 1.007; ηp2=0.035), range of combined motion (plantar and dorsiflexion) of right ankle joint (p = 0.088; ηp2=0.170) and range of motion of left hip extension (p = 0.158; ηp2=0.060). The participants of CG statistically significantly differed from EG1, EG2, and EG3 in the squat performance after the applied treatment. Discussion The effect of the treatment was the occurrence of a transformational processes in almost all measured variables. It can be concluded that the integrative method is effective and applicable in practice for both young adults and recreational athletes.